Time Series Analysis of Temperature and Rainfall Data of Dhaka Division (Dhaka University Journal of Science, 2017)
In this paper, thirty five years’ (1981-2015) temperature and rainfall data have been studied to detect the recent trends in temperature and rainfall over Dhaka division of Bangladesh. Data of climatic factors such as annual average maximum temperature (MAXT), minimum temperature (MINT), mean temperature (MEANT), monsoon total rainfall (MTR) and annual total rainfall (ATR) have been analyzed. Sen’s non-parametric estimator of slope has been frequently used to estimate the magnitude of trend, whose statistical significance is assessed by the Mann–Kendall test. For this purpose, data from four meteorological stations (Dhaka, Mymensingh, Tangail and Faridpur) have been used. It is observed that annual average maximum, minimum and mean temperature of the study area are increasing at the rates 0.0170C/year, 0.0090C/year and 0.0130C/year respectively and the upward trend is statistically stable with 10% level of significance. On the other hand, monsoon total rainfall and annual total rainfall are decreasing at the rates of 4.94 mm/year and 16.11mm/year respectively where the downward trend of MTR is insignificant but the trend of ATR is significant with 10% level of significance.Dhaka Univ. J. Sci. 65(2): 119-123, 2017 (July)